Succinylated Bacterial Cellulose Induce Carbonated Hydroxyapatite Deposition in a Solution Mimicking Body Fluid - Farah Nurlidar; Mime Kobayashi (Indonesian Journal of Chemistry, 2019)
Incorporation of bone-like hydroxyapatite into bacterial cellulose (BC) is an attractive approach for the fabrication of a bioactive three-dimensional (3D) scaffold for bone tissue regeneration. This study investigates the influence of the succinylation of BC on its ability to incorporate bone-like hydroxyapatite. A biomimetic process using a 1.5 × Simulated Body Fluid (SBF) was used to deposit the hydroxyapatite into the succinylated-BC. After soaking the succinylated-BC in the 1.5 × SBF for six days, Scanning Electron Microscope (SEM) images were taken and the composition of the succinylated-BC was analyzed by energy dispersive X-ray spectrometry. The biocompatibility of the scaffolds was tested in vitro using rat Bone Marrow Stromal Cells (rBMSCs). The SEM images and Fourier Transform Infrared Spectroscopy (FTIR) spectra showed that carbonated hydroxyapatite was deposited on the succinylated-BC. In contrast, only a small amount of carbonated hydroxyapatite deposition was observed on unmodified BC, indicating that the succinyl group in the BC is effective for inducing hydroxyapatite deposition. In vitro studies using rBMSCs revealed the biocompatibility of the scaffold. Combining with the ability of the cells to differentiate into bone cells, the succinylated-BC scaffold is a promising 3D scaffold for bone tissue regeneration.